Youth health in a digital world: Approaching screen use in clinical practice. (July 2020) - Jericho, Monique; Elliott, April
New technologies, such as smartphones, have altered our behaviours and cultural structures more dramatically than televisions of our past. The array of today's electronic devices have pulled our eyes closer to the screens and our focus further into the boxes behind those screens. Screens may serve us; simultaneously, they are increasingly giving rise to health and social challenges that researchers are only beginning to understand. There is a growing dis-ease among parents and health care providers (HCPs) about how screens are affecting youth. As the push for increased screen time continues in both educational and workplace settings, HCPs are not only tasked with helping parents and youth cope, but they must find ways to manage the impact of increased personal and professional screen time on their own wellbeing. This article considers the impact of increased screen time on two groups: youth and the HCPs supporting them. Furthermore, the authors explore the impact of screen use on clinical interactions, and patient care, suggesting a process for addressing screen use and provide specific tools including a reflective query for HCPs to better evaluate the impact of their own screen usage, 'the Coaching Stance' and TGROW, a questioning approach derived from coaching theory.